Perjuangan Gerakan Buruh Tidak Sekadar Upah: Melacak Perkembangan Isu Gerakan Buruh di Indonesia Pasca Reformasi - Zuhdan, Muhammad (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this paper is to track issues championed by the labor movement after the reform. The firs thesis of this paper behold issue championed labor movement is not merely a matter of wage increases. This paper focus on championed issue by the labor movement in the post-reformation Indonesia. The reasons for selecting this theme is to expand the publicâs view on the issue of labor which has always been synonymous with wage when the labor movement has long roots and a tradition of thought that labor issues are always dialectical and dynamic with the changing socio-political structure. The results of this study indicate that the issue of the labor movement in the post-reformation Indonesia no longer dwell on the issue of wage increase alone but develops progressively in the direction of political issues that is identical to the New Left movement, ranging from labor issues Go Politics, anti-neoliberalism, gender, human rights, democracy, citizenship, public policy, etc.